"It is the One Thing that has Worked": facilitators and barriers to switching to nicotine salt pod system e-cigarettes among African American and Latinx people who smoke: a content analysis - Kim Pulvers; Myra Rice; Jasjit S. Ahluwalia; Michael J. Arnold; Crystal Marez; Nicole L. Nollen (BMC, 2021)
Abstract Background Electronic cigarettes are a harm reduction strategy for individuals who smoke cigarettes who cannot or do not want to quit using FDA-approved cessation methods. Identifying perceived facilitators and barriers to switching among people who smoke cigarettes is critical to optimizing health impact. This is particularly important for the most dominant e-cigarette device, nicotine salt pod electronic cigarettes. We investigate the experience using pod electronic cigarettes among African American and Latinx individuals who smoke, the two largest racial/ethnic minority groups who experience significant health disparities. Methods From July 2018 to May 2019, adults who smoked cigarettes, age 21 + (N = 114; M age = 44.6, 59.6% male, 52.6% African American from Kansas City, 47.4% Latinx from San Diego) received JUUL-brand electronic cigarettes (referred to hereafter as JUUL) for 6 weeks and answered interview questions at week six. We inquired what they liked and disliked about using JUUL, what helped with switching and made switching difficult, future intentions for continued JUUL use, and how JUUL compared to past smoking reduction methods. Responses were coded into themes by independent raters. Theme frequencies were analyzed separately by race/ethnicity and week 6 use trajectory (exclusive JUUL use, dual JUUL and cigarette use, exclusive cigarette use). Results Clean/smell was the aspect of using JUUL most commonly liked (23%), followed by convenience (19%). Coughing/harshness was a more common barrier to switching for African American (44%) than Latinx (9%), and for continuing cigarette use (56%) than for those who exclusively switched or dually used JUUL and combustible cigarettes (15-21%). Most (78% African American; 90% Latinx) reported that the benefits of using JUUL outweighed barriers, and this varied by JUUL use trajectory: 94% exclusive switch, 86% dual use, and 42% continued cigarette use. The majority said they would continue using JUUL to replace cigarettes (83% African American; 94% Latinx) and that JUUL worked better than other methods to reduce cigarettes (72%). Conclusion African American and Latinx individuals who smoked experience using pod electronic cigarettes was generally positive. Understanding facilitators and impediments to switching to electronic cigarettes among racial/ethnic minority people who smoke can inform harm reduction interventions and reduce tobacco-related health disparities. Trial Registration ClinicalTrials.gov Identifier: NCT03511001 posted April 27, 2018.